Implementation Of Ideal Discharge Planning To Improve Patients’ Discharge Readiness At Panti Waluya Sawahan Hospital - Agustina, Clara; Kuswantoro Rusca Putra; Maria Magdalena Sri Widiastuti (Caring: Jurnal Pengabdian Masyarakat, 2025)
Effective discharge planning is a key component in ensuring that patients and families are prepared to continue care after hospital discharge. Limited use of educational media and the inconsistent application of methods that ensuring patients’ have been identified as challenges in the discharge planning process in the Placida Paviliun Ward of Panti Waluya Sawahan Hospital. This community service activity aimed to implement IDEAL Discharge Planning as a structured approach developed by the Agency for Healthcare Research and Quality to improve patient discharge readiness. The activity was conducted from October to November 2025 and involved six patients. The method consisted of three stages: preparation, implementation, and evaluation. The preparation stage included the development of an educational module, standard operating procedures, assessment instruments, and educational media based on six major diagnoses. The implementation stage involved initial assessment of patients’ educational needs, delivery of personalized daily education, and education provided prior to discharge. Evaluation was conducted using a discharge readiness instrument covering home care ability, caregiver identification, medication management, recognition of warning signs, and follow-up planning. The results showed that all patients demonstrated improved discharge readiness following the implementation of IDEAL Discharge Planning. This activity demonstrates that applying IDEAL Discharge Planning supported by needs-based educational media and family involvement can strengthen patients’ readiness to perform self-care at home. This model has the potential to be implemented in other inpatient units to improve quality of care transitions.